Dragon Fruit Foliage: An Agricultural Cellulosic Source to Extract Cellulose Nanomaterials - Tuyet Phung Thi Anh; Toan Viet Nguyen; Phuong Thi Hoang; Phuong Vu Thi; Thoa Nguyen Kim; Quyen Nguyen Van; Chien Nguyen Van; Yen Dao Hai (Molecules, 2021)
In this report, we focus our effort to extract cellulose nanomaterials (CNs) from an agricultural cellulosic waste, Dragon Fruit foliage (DFF). DFF was first pretreated by several mechanical treatments and then bleached by chemical treatment to obtain bleached DFF. CNs were then produced from the hydrolysis of the bleached DFF catalyzed by sulfuric acid. We obtained CNs with a small diameter (50 to 130 nm) and length (100 to 500 nm) and a height of 3 to 10 nm. The CNs have a high crystallinity (crystallinity index 84.8%), high −COOH content (0.74 mmol·g−1), good thermal stability and a good Cu (II) adsorption capacity with an adsorption maximum of ~103 mg·g−1. These findings demonstrated the great potential of converting many agricultural cellulosic wastes into valuable cellulose nanomaterials.